Comparative observation of the flow behavior of low- and high-temperature ashes of biomass. (1st November 2022) - Li, Jiazhu; Wei, Juntao; Reinmöller, Markus; Liang, Chen; Li, Shuangshuang; Xiao, Ruirui; Xu, Jie
Highlights: Associated release of K and Cl and related formation of mineral phases are observed. Flow behavior of low-temperature and high-temperature ash of biomass is investigated. Both ashes show flow temperature below 1100 °C fitting entrained-flow gasification. Rarely observed higher ash fusion temperatures are detected for LTA than for HTA. The significant slag formation below AFT and viscosity-driven behavior are concluded. Abstract: Biomass ashes are frequently known for their limiting effects in thermochemical conversion processes. Thus, a comprehensive understanding and prediction of the temperature-depending behavior of the ashes is indispensable for practical applications. In the present study, the flow behavior of low-temperature ash (LTA) and high-temperature ash (HTA) of biomass is investigated in detail and monitored by in situ methods. For this purpose, the mineral matter formation and transformation of both ashes are studied by X-ray diffraction (XRD) and X-ray fluorescence (XRF) analysis. A combination of heating-stage microscope and scanning electron microscope equipped with energy-dispersive X-ray spectroscopy (SEM-EDX) has enabled a systematic identification of the microstructures and observations of LTA and HTA. The results have illustrated an associated release of K and Cl and the formation of new mineral phases in the remaining material during ashing at increased temperature. Both ashes have exhibited flow temperatures below 1100 °C and a rarely observed behavior of higher characteristic temperatures for LTA than for HTA is detected. From the heating-stage microscopy, the ashes have given evidence to a significant formation of slag at the characteristic temperatures and a viscosity-driven behavior at the characteristic points of ash fusion. Based on these results, a conclusion can be drawn regarding the usability of this biomass for high-temperature conversion processes on the industrial scale.